2019
DOI: 10.1002/sia.6649
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dielectric layer on the thermal boundary resistance of GaN‐on‐diamond substrate

Abstract: The cooling behavior of GaN‐on‐diamond substrate can be enhanced by reducing the thermal boundary resistance (TBR), which is mainly determined by the nature of interlayer. Although SiN film is considered as the primary candidate of dielectric layer, it is still needed to be optimized. In order to facilitate the understanding of the influence of dielectric layer on the TBR of GaN‐on‐Diamond substrate, aluminum nitride (AlN), and silicon nitride (SiN) film were compared systematically, both of which are 100 nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…The present paper aims to demonstrate that certain reconstruction patterns involving substitutional atoms can improve the energetic stability of the diamond-GaN interfaces, as was observed in the case of diamond-AlN interfaces [26]. Since the proposed reconstruction patterns take place in the GaN substrate, our findings are closely related to GaN-on-diamond experimental approaches where the formation of carbide bonds [27] or a silicon-carbon-nitrogen layer between GaN and diamond [16] was reported.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…The present paper aims to demonstrate that certain reconstruction patterns involving substitutional atoms can improve the energetic stability of the diamond-GaN interfaces, as was observed in the case of diamond-AlN interfaces [26]. Since the proposed reconstruction patterns take place in the GaN substrate, our findings are closely related to GaN-on-diamond experimental approaches where the formation of carbide bonds [27] or a silicon-carbon-nitrogen layer between GaN and diamond [16] was reported.…”
Section: Introductionsupporting
confidence: 64%
“…In turn, in the experiments on the diamond growth on the GaN covered with a SiN dielectric layer [16], it was concluded that a few-nanometer-thick Si-rich SiN layer could convert to SiC before diamond nucleation, and Si-C bonding during diamond nucleation was beneficial to the strong adhesion of the obtained diamond films.…”
Section: Influence Of Point Defects On the Stability Of The Diamond-gan Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time the bottleneck of the heat extraction was recognized to be the TBR between GaN and diamond (TBR GaN/diamond ) [72] and most of following research focused on decreasing it, whether by decreasing the dielectric thickness, by using a different dielectric, or by optimizing the diamond nucleation layer [10,[72][73][74][75][76][77][78][79][80][81][82][83][84]. The impact of the thickness of the GaN buffer layer on the R th of the HEMT devices [85][86][87][88][89][90] and the effects of the stress caused by the difference in the CTEs of GaN and diamond [91][92][93][94][95][96] were also evaluated by different research groups.…”
Section: Gan-on-diamondmentioning
confidence: 99%
“…Free standing diamond has also been used as a sub-mount for lasers [16], [17] as well as a circuit board integrated with water-cooling channels [18]. Gallium nitride (GaN) high electron mobility transistors (HEMTs) also benefit from the integration with diamond films [19]- [23].…”
Section: Introductionmentioning
confidence: 99%